2002
DOI: 10.1200/jco.2002.07.146
|View full text |Cite
|
Sign up to set email alerts
|

Response to Neoadjuvant Chemotherapy Combined With Regional Hyperthermia Predicts Long-Term Survival for Adult Patients With Retroperitoneal and Visceral High-Risk Soft Tissue Sarcomas

Abstract: Response to neoadjuvant chemotherapy combined with RHT is predictive for an improved local tumor control resulting in a long-term survival benefit for patients with HR-STS at unfavorable RP/V sites; however, the impact of RHT has to be defined in a randomized phase III trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 32 publications
0
43
0
7
Order By: Relevance
“…[1][2][3][4] Preoperative chemotherapy cannot be regarded as standard treatment to date; however, in 1996, available data justified the initiation of a European Organization for Research and Treatment of Cancer (EORTC) Phase III trial on neoadjuvant chemotherapy alone versus chemotherapy in conjunction with regional hyperthermia (RHT). 5,6 Today, RHT represents a standardized treatment option that usually is applied as an adjunct to radiotherapy and/or chemotherapy. In a number of Phase II and III trials, it has been shown that RHT improved local control in various locally advanced tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Preoperative chemotherapy cannot be regarded as standard treatment to date; however, in 1996, available data justified the initiation of a European Organization for Research and Treatment of Cancer (EORTC) Phase III trial on neoadjuvant chemotherapy alone versus chemotherapy in conjunction with regional hyperthermia (RHT). 5,6 Today, RHT represents a standardized treatment option that usually is applied as an adjunct to radiotherapy and/or chemotherapy. In a number of Phase II and III trials, it has been shown that RHT improved local control in various locally advanced tumors.…”
Section: Resultsmentioning
confidence: 99%
“…This also has been demonstrated in patients with STS. 6,23 The impressive correspondence between !90% tumor necrosis (or even a pathologic complete response) and T 90 (or T 50 ) and the striking superiority of the hyperthermia group compared with the control group suggest a contribution of RHT to the local efficacy. Clearly, this can be clarified only by the final results from the ongoing EORTC-ESHO study.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is difficult because of the proximity of vital structures of the retroperitoneal and adjacent vascularities. These affect local recurrence, postoperative outcomes and long-term survival rates [1,2] . A retrospective review of 143 cases of APRT in the First Affiliated Hospital of China Medical University was performed to analyze the factors influencing postoperative outcomes and optimize treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In another retrospective analysis for retroperitoneal and visceral STS recruited to both studies, the RHT-91 and RHT-95 protocols demonstrated that the initial response to chemotherapy combined with RHT was predictive of long-term survival. 13 Most recently, under the auspices of the EORTC and the European Society of Hyperthermic Oncology (ESHO), we were able to complete a randomised intergroup phase III trial (EORTC 62961/ESHO RHT-95) of multimodal treatment in patients with primary (S1 group) and recurrent (S2 group) disease or after inadequate surgery (S3 group: resections with HR-STS to extremity and non-extremity received neoadjuvant systemic chemotherapy (four cycles of the EIA regimen) and were randomised to one of two arms -chemotherapy alone or combined with RHT -followed by definitive surgery and radiotherapy. Thereafter, in addition, four cycles of the EIA regimen were administered with or without RHT, according to the initial randomisation (see Figure 2).…”
Section: Regional Hyperthermia Combined With Chemotherapymentioning
confidence: 99%